2014
DOI: 10.1140/epjc/s10052-014-2981-5
|View full text |Cite
|
Sign up to set email alerts
|

QCD and strongly coupled gauge theories: challenges and perspectives

Abstract: We highlight the progress, current status, and open challenges of QCD-driven physics, in theory and in experiment. We discuss how the strong interaction is intimately connected to a broad sweep of physical problems, in settings ranging from astrophysics and cosmology to strongly coupled, complex systems in particle and condensed-matter physics, as well as to searches for physics beyond the Standard Model. We also discuss how success in describing the strong interaction impacts other fields, and, in turn, how s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
436
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 494 publications
(455 citation statements)
references
References 2,511 publications
(2,121 reference statements)
8
436
0
5
Order By: Relevance
“…Interested readers may also consult reviews in Refs. [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,39].…”
Section: General Status Of Hadron Spectroscopymentioning
confidence: 99%
“…Interested readers may also consult reviews in Refs. [40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,39].…”
Section: General Status Of Hadron Spectroscopymentioning
confidence: 99%
“…[31] (see also e.g. [32][33][34] for some details of the QCD calculations of the quark-antiquark potential).…”
Section: Jhep12(2016)122mentioning
confidence: 99%
“…Correcting for this was finally seen to exactly cancel the constant IR term from the unresummed spectral function, while leaving its earlier, correct UV behavior intact. 5 Having obtained both the unresummed and (partially) HTL resummed spectral functions, we proceeded to study their behavior as well as their effect on the imaginary time shear correlator. We observed that the resummation only affects the spectral function at very small ω, and that the deviation of our new imaginary time correlator from the one derived in [24] is in practice negligible.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5]). Despite the strong experimental and phenomenological motivation, a nonperturbative first principles tool to predict its value is, however, still lacking, even though an extensive amount of work has been devoted to the topic in the weak coupling [6,7], lattice [8][9][10] and gauge/gravity frontiers [11][12][13].…”
Section: Introductionmentioning
confidence: 99%